A Short Pulse, Narrow Band Distributed Feedback Dye Laser Using Nanoparticle-doped Dye Solution Active Medium - An, Nguyen Thi My; Lien, Nghiem Thi Ha; Duong, Vu; Thuy, Nguyen Thanh; Hoa, Do Quang (Communications in Physics, 2014)
Spherical gold nanoparticles doped dye solution was used for laser active medium. Fluorescence and absorption spectral shapes of laser dye molecules were modified by the resonance energy transfer between gold nanoparticles due to localized surface plasmon effect. Laser pulse width and tuning range of a distributed feedback dye laser can be controlled by using various gold nanoparticle concentrations. The gold nanoparticles can be considered as a quenching element inside laser cavity to remove relaxation oscillation pulses at high pumping rate above threshold.